Effects of aging and soil properties on zinc oxide nanoparticle availability and its ecotoxicological effects to the earthworm Eisenia andrei. (21st July 2016) - Romero‐Freire, Ana; Lofts, Stephen; Martín Peinado, Francisco J.; van Gestel, Cornelis A.M.
Abstract: To assess the influence of soil properties and aging on the availability and toxicity of zinc (Zn) applied as nanoparticles (Zn oxide [ZnO]‐NPs) or as Zn 2+ ions (Zn chloride [ZnCl2 ]), 3 natural soils were individually spiked with either ZnO‐NPs or ZnCl2 and incubated for up to 6 mo. Available Zn concentrations in soil were measured by porewater extraction (ZnPW), whereas earthworms ( Eisenia andrei ) were exposed to study Zn bioavailability. Porewater extraction concentrations were lower when Zn was applied as NPs compared to the ionic form and decreased with increasing soil pH. For both Zn forms and Zn‐PW values were affected by aging, but they varied among the tested soils, highlighting the influence of soil properties. Internal Zn concentration in the earthworms (ZnE) was highest for the soil with high organic carbon content (5.4%) and basic pH (7.6) spiked with Zn‐NPs, but the same soil spiked with ZnCl2 showed the lowest increase in ZnE compared to the control. Survival, weight change, and reproduction of the earthworms were affected by both Zn forms; but differences in toxicity could not be explained by soil properties or aging. This shows that ZnO‐NPs and ZnCl2 behave differently in soils depending on soil properties and aging processes, but differences in earthworm toxicity remain unexplained. Environ Toxicol Chem 2017;36:137–146. © 2016 SETAC